Exercises in probability : a guided tour from measure theory to r andom processes, via conditioning - Chaumont, L. (Loic); Yor, Marc. (Cambridge ; New York : Cambridge University Press, New York : New York : New York, 2012)
"Derived from extensive teaching experience in Paris, this second ed ition now includes over 100 exercises in probability. New exercises hav e been added to reflect important areas of current research in probabil ity theory, including infinite divisibility of stochastic processes, pa st-future martingales and fluctuation theory. For each exercise the aut hors provide detailed solutions as well as references for preliminary a nd further reading. There are also many insightful notes to motivate th e student and set the exercises in context"--
Includes bibliographical references (p. 270-277) and index.
Keywords: Probabilities. -- Problems, exercises, etc; Probabilities -- Problems, exercises, etc